THE PECULIARITIES OF TEACHING AN IDEOGRAPHIC LANGUAGE. TEACHING READING IN CHINESE - Moshurenko, Mariia; Naumenko, Stanislav; Ruda, Nataliia; Siekina, Nataliia; Zhukova, Kateryna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Reading plays an important role in the educational process, as it is one of the central spheres in communication in a foreign language. However, reading Chinese has its own peculiarities, because the method of writing differs from the phonetic languages. The paper is devoted to the teaching reading in Chinese for beginners, using the peculiarities of an ideographic language. The outlining of these peculiarities and the development of exercises, with the consideration of these peculiarities are relevant, because most of the methodological developments are devoted to the teaching of reading phonetic languages. The paper aims to determine the peculiarities of teaching reading in Chinese, which are caused by the ideographic character of the hieroglyphic writing. The developed system of exercises for teaching reading in the Chinese language for beginners is provided. The exercises enable learners to get acquainted with the hieroglyphic writing, to build a grapheme competence and to learn how to write any character.